Infrastruktur PAUD di Indonesia: Antara Standar Ideal dan Realita Lapangan - Hijriyani, Yuli Salis; Ragil, Yoga Aditia; Utami, Fitria Budi (Institut Agama Islam Negeri Ponorogo, 2025)
The government has established various policies and national standards related to facilities and infrastructure for PAUD, but implementation in the field still shows significant gaps, especially in areas with geographical limitations. This study aims to assess the infrastructure condition of PAUD institutions in Subang District, as well as identify challenges and efforts made in meeting ideal standards. The method used is a qualitative case study with data collection through interviews, observation, and documentation. Participants in this study consisted of PAUD teachers and representatives of the local education office. The results show that infrastructure limitations such as lack of proper classrooms, sanitation and play areas are still a major issue. These challenges are exacerbated by budget constraints, difficult geographical locations, and suboptimal cross-sector support. The findings confirm the importance of more contextualized policies, cross-sectoral collaboration and strengthened infrastructure support to realize inclusive and quality ECD in all regions of Indonesia.